2020
DOI: 10.1093/rheumatology/keaa392
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil for methotrexate-resistant juvenile localized scleroderma

Abstract: Objectives To investigate safety and efficacy of MMF in patients with severe or MTX-refractory juvenile localized scleroderma. Methods Consecutive juvenile localized scleroderma patients undergoing systemic treatment were included in a retrospective longitudinal study. Patients treated with MMF because they were refractory or intolerant to MTX (MMF-group) were compared with responders to MTX (MTX-group). Disease activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
2
12
0
2
Order By: Relevance
“…Since the prior elicitation exercise, two further retrospective studies provide further evidence for the efficacy, safety and tolerability of MMF in LS. A case series of MMF in 22 patients with JLS compared to 47 on MTX showed no significant difference in relapse-free survival between the groups although MMF appeared to induce more persistent remission, and MMF was well tolerated 40 . In a study of 77 participants (all 16 years or older), MMF was well tolerated with 35% achieving disease remission 52 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Since the prior elicitation exercise, two further retrospective studies provide further evidence for the efficacy, safety and tolerability of MMF in LS. A case series of MMF in 22 patients with JLS compared to 47 on MTX showed no significant difference in relapse-free survival between the groups although MMF appeared to induce more persistent remission, and MMF was well tolerated 40 . In a study of 77 participants (all 16 years or older), MMF was well tolerated with 35% achieving disease remission 52 .…”
Section: Discussionmentioning
confidence: 93%
“…It is an easy to use skin score which can be completed by clinicians in the clinic room without specialist equipment. Reliability has been tested in several cohorts including adults and as an outcome measure in clinical trials 8,[40][41][42][43][44] . The mLoSSI activity component was chosen as the measure of efficacy for the consensus meeting.…”
Section: Establishment Of Primary Outcome Measure and Consensus Agreement On Key Elements Of Trial Designmentioning
confidence: 99%
“…The majority of patients improved, with 35% of adults and 91% of jLS in remission at last follow-up (13.5 months, 9.4 years, respectively). Although 46% of jLS patients relapsed at a mean time of 31 months, most still achieved disease control, with 50% able to remain in remission off MMF at last follow-up [30 ▪ ]. Studies reported a 10–55% frequency of adverse events but this rarely led to discontinuation of MMF (0–16%).…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%
“…Mycophenolate mofetil (MMF), used either as monotherapy or combination therapy as first‐line treatment or after typical standard of care treatments had failed, led to disease remission in 27 of 77 (35%) of adult and pediatric patients with morphea in a single retrospective cohort study 137 . In another study, 90.9% of children who were refractory or intolerant to MTX achieved sustained remission with MMF at the end of the follow‐up period of 9.4 years 138 . Case reports have described clinical improvement with the use of cyclosporine, 139 tocilizumab, 140 TNF‐α inhibitors, 141,142 tofacitinib, 143,144 and abatacept 145,146 …”
Section: Treatmentmentioning
confidence: 99%
“…137 In another study, 90.9% of children who were refractory or intolerant to MTX achieved sustained remission with MMF at the end of the follow-up period of 9.4 years. 138 Case reports have described clinical improvement with the use of cyclosporine, 139 tocilizumab, 140 TNFα inhibitors, 141,142 tofacitinib, 143,144 and abatacept. 145,146…”
Section: Tre Atmentmentioning
confidence: 99%